Correlation of Coronary Angiographic Severity with Carotid intima Media Thickness and Flow mediated dilatation of brachial Artery in Patients with Ischemic Heart Disease (Cardiovascular Journal, 2013)
Background: Ischemic Heart Disease which encompasses Acute Coronary Syndrome and Chronic Stable Angina is the most common cause of worldwide mortality and morbidity. Carotid intima media thickness (CIMT) is a non-invasive ultrasonographic technique to image the carotid arteries which measures the thickness of the intima and media of these vessels. It is a marker of atherosclerotic process. Flow mediated dilatation (FMD) is a marker of endothelial function of arteries. Ischemic heart disease can be predicted long before its actual occurrence by observing these two phenomenons. Methods: This cross sectional study done in the Department of Cardiology, Dhaka Medical College Hospital during the period of Oct 2010- Sept 2011.We enrolled 102 patients admitted with IHD by purposive sampling. We assessed FMD of brachial artery, CIMT by vascular duplex. Coronary artery disease severity was assessed by vessel score, stenosis score and extent score from angiography. Results:The mean (±SD) age of the patients was 50.9(±11.3) years. The male- female ratio was 5:1. CIMT has significant negative correlation with FMD (r=-.407, p=